LANGUAGE EXPRESSION TRADERS BUY AND SELL INTERACTIONS IN THE KMGD TEBUIRENG MARKET - SucI Armala (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The purpose of this study is to find and explain the language of traders in the interaction of buying andselling in the Kawasan Makam Gus Dur Tebuireng Jombang (KMGD) market. The research method used is adescriptive qualitative approach. The data collection techniques used were: 1. Technique survey, 2. Recordingtechnique, 3. Listening technique and 4. Note technique. The data analysis technique uses the followingtechniques: 1. Data collection, 2. Data reduction, 3. Data presentation, 4. Conclusing drawing / verification. In thisstudy, the validity of the data used data triangulation: 1. Technique triangulation, 2. Time triangulation. Theresults of the research that can be formulated that the language expressions used by merchants are Javanese,Indonesian and Madurese.